Thrombocytosis is associated with increased short and long term mortality after exacerbation of chronic obstructive pulmonary disease: a role for antiplatelet therapy?. Issue 7 (17th April 2014) - Harrison, Michelle T; Short, Philip; Williamson, Peter A; Singanayagam, Aran; Chalmers, James D; Schembri, Stuart
Abstract : Introduction: Evidence suggests that platelets play a significant role in inflammation in addition to their role in thrombosis. Systemic inflammation is linked to poor short and long term outcomes in COPD. Increased platelet activation has been reported in acute exacerbations of COPD (AECOPD). We investigated whether thrombocytosis is independently associated with poor outcomes following AECOPD. Methods: An observational cohort study of patients hospitalised with AECOPD was performed. Patients were >40 years with spirometry confirmed COPD admitted between 2009 and 2011. Platelet count was recorded on admission. The primary outcome was 1-year all-cause mortality. Secondary outcomes included inhospital mortality and cardiovascular events. Analyses were conducted using logistic regression after adjustment for confounding variables. Results: 1343 patients (49% male) were included. Median age was 72 years (IQR 63–79 years). 157 (11.7%) had thrombocytosis. Thrombocytosis was associated with both 1-year mortality and inhospital mortality; OR 1.53 (95% CI 1.03 to 2.29, p=0.030) and OR 2.37 (95% CI 1.29 to 4.34, p=0.005), respectively. Cardiovascular hospitalisation was not significantly increased (OR 1.13 (95% CI 0.73 to 1.76, p=0.600)) in patients with thrombocytosis. Aspirin or clopidogrel treatment correlated with a reduction in 1-year mortality (OR 0.63 (95% CI 0.47 to 0.85, p=0.003)) but not inhospital mortality (OR 0.69 (95% CI 0.41 to 1.11, p=0.124)). Conclusions: After adjustment for confounders thrombocytosis was associated with increased 1-year mortality after exacerbation of COPD. Antiplatelet therapy was associated with significantly lower 1-year mortality and may have a protective role to play in patients with AECOPD.